New Pain Management Procedure after Total Knee Arthroplasty: Gonyautoxins are Safe and Effective after A Single Intra-Articular Infiltration - Hinzpeter, Jaime; Barrientos, Cristián; Barahona, Maximiliano; Zamorano, Álvaro; Palet, Miguel; Wulf, Rodrigo; M. Sepúlveda, Joaquín; Bustamante, Tamara; Piron, Robin; del Campo, Miguel; Lagos, Nestor (International Physiology Journal, 2018)
Objective To evaluate the effect of a single intraarticular dose of Gonyautoxins for pain control after Total Knee Arthroplasty (TKA). Subjects 30 consecutive patients with osteoarthritis with Kellgren & Lawrence level of two or more, who required TKA, were enrolled. Methods Subjects receive a single intra-articular infiltration of 40 µg dose of Gonyautoxins, immediately after TKA wound closure. The pain was measured with the Visual Analog Scale (VAS). Additionally, the range of motion at 12, 36, and 60 hours and hospital stay length were recorded. Results were compared to the 2014 TKA cohort. Results 25 patients (83.33%) achieved successful pain management. All patients achieved complete flexion ≥90° 60 hours after surgery and 24 patients achieved full extension before hospital discharge. The median VAS pain score for each evaluation period was ≥2. The 25 Gonyautoxins treated patients who achieved successful pain management had a median VAS pain score of 0 after 36 and 60 hours. Conclusions Gonyautoxins are safe and effective in pain management after TKA when used as a single intra-articular dose. This protocol shows adequate pain control in TKA, reducing discharge to 3 days and greater range of motion, improving the post-operated patient experience.
Keywords: Paralytic Shellfish Poisoning; Gonyautoxins; intra-articular infiltration; Total knee arthroplasty; pain management.